The concept of measure, from Plato to modern statistics. Art of living or intellectual principle? - Paola Monari (Statistica, 2007)
This paper purports to show that the statistical concept of "measure" was advanced right from the origins of western thought: from the philosophical speculation of Plato, to the harmonic numerical relationships of Pythagoras. We must wait until the sixteenth century for a modern definition, when Galileo takes measurement away from the domain of shops and merchants and brings it to the realm of experimental science. It is Galileo too, who begins to delineate the statistical theory of errors which was further developed in the following centuries. Finally, in the nineteenth century, Kant distinguishes between extensive and intensive quantities; the letter do not possess the materiality which is required by physics, but which can still be measured. And so "psycomentrics" was conceived; the horizons of research were widened, and science recognised that everything can be measured, uncertainty, risk and indeterminismess too. So, science conquers probability as a powerful means of measurement in the vast world of uncertainty.